2021
DOI: 10.3390/healthcare9101281
|View full text |Cite
|
Sign up to set email alerts
|

Community Pharmacists’ Perceptions towards the Misuse and Abuse of Pregabalin: A Cross-Sectional Study from Aseer Region, Saudi Arabia

Abstract: Pregabalin is a first-line therapy for neuropathic pain and for chronic pain. It has abuse potential. This study was conducted to assess community pharmacists’ perceptions towards pregabalin abuse and misuse in the Aseer region, Saudi Arabia, and identify predictors and associated factors. A cross-sectional survey using a structured questionnaire following a self-administrative study was conducted across community pharmacies in the Aseer region (Abha, Khamis Mushait, Mahayel, Sarat Abeeda, Ahad-Rufaida, and Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Another cross-sectional survey was conducted to explore pharmacists knowledge and practices regarding painkillers at King Abdul-Aziz Medical City-Central Region. 36 The learning and experience of pharmacists of the practices and information were also assessed by Wajid (2015). The survey findings showed that amongst the surveyed pharmacists, approximately two-thirds (63.6%) were completely confident, while 32% were moderately confident, and a solitary 4.5% were not confident at all.…”
Section: Discussionmentioning
confidence: 99%
“…Another cross-sectional survey was conducted to explore pharmacists knowledge and practices regarding painkillers at King Abdul-Aziz Medical City-Central Region. 36 The learning and experience of pharmacists of the practices and information were also assessed by Wajid (2015). The survey findings showed that amongst the surveyed pharmacists, approximately two-thirds (63.6%) were completely confident, while 32% were moderately confident, and a solitary 4.5% were not confident at all.…”
Section: Discussionmentioning
confidence: 99%
“…One Saudi study assessed their knowledge, attitude and beliefs about such drugs and the majority of community pharmacists reported to have received training to identify drug abuse during their pharmacy education and could appropriately counsel suspected customers ( Mobrad et al, 2020 ). Recently, a study from the south-western region of Saudi Arabia evaluated the perceptions of community pharmacists regarding consumption of pregabalin and found that nearly two-thirds of their respondents suspected pregabalin to be abused ( Alshahrani et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%